Game Theory: Mathematical Approaches and Applications - Ferreira, M. A. M. (2023)
The main goal of Game Theory is the study of mathematical models of strategic interaction between rational decision makers. It has applications in all fields of social sciences, as well as in logic, systems science and computer science. Game Theory today applies to a myriad of behavioral relationships, and is now a comprehensive term for the science of logical decision-making in humans, animals and computers. Thus, it is also called “science of strategy”. Whether in the definition of concepts and development of theory, or in the construction of conceptual models for applications in practical life, Game Theory has led to the use and construction of very interesting mathematical models. We would like to invite you to submit your work for the Special Edition “Game Theory: Mathematical Approaches and Applications”. This special issue seeks high quality contributions in the mathematical formulation of Game Theory concepts and tools, and also in its application to the modeling and study of practical situations.